The BEACON study: protocol for a cohort study as part of an evaluation of the effectiveness of smartphone-assisted problem-solving therapy in men who present with intentional self-harm to emergency departments in Ontario - Hatcher, Simon; Heisel, Marnin; Ayonrinde, Oyedeji; Campbell, Julie K; Colman, Ian; Corsi, Daniel J; Edgar, Nicole E; Gillett, Lindsay; Kennedy, Sidney H; Hunt, Sophia L; Links, Paul; MacLean, Sarah; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Patients who present to emergency departments after intentional self-harm are at an increased risk of dying by suicide. This applies particularly to men, who represent nearly two-thirds of those who die by suicide in Ontario. One way of potentially addressing this gap is to offer a course of blended problem-solving therapy, comprised of a brief course of evidence-based psychotherapy for individuals at risk for suicide, facilitated by the use of a patient-facing smartphone application and a clinician-facing “dashboard.” This approach has the potential to combine the benefits of face-to-face therapy and technology to create a novel intervention. Methods This is a cohort study nested within a larger pragmatic multicentre pre- and post-design cluster randomised trial. Suicidal ideation assessed by the Beck Scale for Suicide Ideation is the primary outcome variable. Secondary outcome measures include depression (Patient Health Questionnaire-9), anxiety (Generalized Anxiety Disorder 7-item scale), post-traumatic stress disorder (Primary Care PTSD Screen), health-related quality of life (EuroQol 5-dimension 5-level questionnaire), meaning in life (Experienced Meaning in Life Scale), perceived social supports (Multidimensional Scale of Perceived Social Support), alcohol use (Alcohol Use Disorders Identification Test), drug use (Drug Abuse Screening Test Short Form 10), problem-solving skills (Social Problem-Solving Inventory–Revised Short Form), and self-reported healthcare costs, as well as health service use measured using Ontario administrative health data. A process evaluation will also be conducted following study completion. Discussion The cohort study will test whether better adherence to the intervention results in better outcomes. The value of the cohort study design is that we can examine in more detail certain subgroups or other variables that are not available in the larger cluster randomised trial. This trial will aim to improve standards by informing best practice in management of men who self-harm and present to hospitals in Ontario. Trial registration ClinicalTrials.gov , NCT03473535 . Registered on March 22, 2018.